Modification of chitosan and chitosan succinate by surfactants and investigation of their properties - Harutyunyan, L.R.; Harutyunyan, R.S.; Gabrielyan, G.A.; Lasareva, E.V. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2019)
[Display omitted] •Surface active complexes of chitosan and chitosan succinate have been prepared.•Сhitosan modified by an anionic surfactant HOS has more surface activity than an amphoteric chitosan succinate modified by different surfactants.•Biocompatible food emulsifiers may be prepared on the base of new derivatives. The modification of chitosan (Ch) with a surfactant hexadecyl-oligo-oxyethylene hemisuccinate (HOS) as well as properties of modified chitosan succinate (ChS) have been studied. Modification of ChS was made with the use of surfactants of different nature: anionic surfactant - sodium dodecyl sulfate, cationic surfactant - dodecyl pyridinium chloride and nonionic surfactant - oxyethylatedcetyl alcohol. The hydrophobically modified Ch (HCh) and ChS derivatives have high surface activity and stabilize oil-in-water emulsions very effectively. It was shown that the hydrophobization of ChS via interaction between ChS and surfactants differs significantly from hydrophobic modification of Ch by anionic surfactants. It is proposed that such difference should be connected with polyampholyte properties of ChS.